2009
DOI: 10.1016/j.jen.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Adherence Strategies and Challenges in Poison Control Communication

Abstract: Introduction-The principal objective of this study was to characterize how nurses and pharmacists at a poison control center (PCC) determine the likelihood of caller adherence to a health care facility referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Findings from this study also suggest that SPIs are likely to be receptive to the idea of improving their skills; they made numerous comments that support the need for a communication training program. This is consistent with studies in which other telehealth providers were open to and supportive of communication training opportunities (Derkx et al, 2009; Ellington et al, 2009; Purc-Stephenson & Thrasher, 2010). It appears that a communication training would be most helpful before actually engaging in telehealth services, to be supplemented by periodic trainings to help strengthen and sustain telephone communication skills (Purc-Stephenson & Thrasher).…”
Section: Discussionsupporting
confidence: 90%
“…Findings from this study also suggest that SPIs are likely to be receptive to the idea of improving their skills; they made numerous comments that support the need for a communication training program. This is consistent with studies in which other telehealth providers were open to and supportive of communication training opportunities (Derkx et al, 2009; Ellington et al, 2009; Purc-Stephenson & Thrasher, 2010). It appears that a communication training would be most helpful before actually engaging in telehealth services, to be supplemented by periodic trainings to help strengthen and sustain telephone communication skills (Purc-Stephenson & Thrasher).…”
Section: Discussionsupporting
confidence: 90%
“…Although we have identified studies that have explored patient adherence to PC recommendations [30][31][32], to our knowledge, no study to date has explored the barriers to and facilitators of clinician adherence to PC recommendations. A few studies have identified beliefs that influence practice guidelines implementation among intensivists [12,[33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…However, SPIs report making a rapid initial assessment of case severity. 12 These provider severity perceptions have been found to affect emergency telehealth providers’ decision making processes. 13 Effective and efficient communication is essential to ensure that poison exposures have a positive patient outcome and is critical in the most serious poison exposures where the stakes are the highest.…”
Section: Introductionmentioning
confidence: 99%